Evaluation of radiation-related invasion in primary patient-derived glioma cells and validation with established cell lines: impact of different radiation qualities with differing LET - Wank, M.; Schilling, D.; Reindl, Judith; Meyer, B.; Gempt, Jens; Motov, S.; Alexander, F.; Wilkens, J. J.; Schlegel, Jurgen; Schmid, T. E.; Combs, S. E. (Journal of Neuro-Oncology, 2018)
Purpose: Glioblastoma multiforme (GBM) is the most common primary brain tumor and has a very poor overall prognosis. Multimodal treatment is still inefficient and one main reason is the invasive nature of GBM cells, enabling the tumor cells to escape from the treatment area causing tumor progression. This experimental study describes the effect of low- and high-LET irradiation on the invasion of primary GBM cells with a validation in established cell systems. Methods: Seven patient derived primary GBM as well as three established cell lines (LN229, LN18 and U87) were used in this study. Invasion was investigated using Matrigel® coated transwell chambers. Irradiation was performed with low- (X-ray) and high-LET (alpha particles) radiation. The colony formation assay was chosen to determine the corresponding alpha particle dose equivalent to the X-ray dose. Results: 4 Gy X-ray irradiation increased the invasive potential of six patient derived GBM cells as well as two of the established lines. In contrast, alpha particle irradiation with an equivalent dose of 1.3 Gy did not show any effect on the invasive behavior. The findings were validated with established cell lines. Conclusion: Our results show that in contrast to low-LET irradiation high-LET irradiation does not enhance the invasion of established and primary glioblastoma cell lines. We therefore suggest that high-LET irradiation could become an alternative treatment option. To fully exploit the benefits of high-LET irradiation concerning the invasion of GBM further molecular studies should be performed.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Brain tumor; Glioblastoma multiforme; Invasion; Irradiation; Primary cells; Survival